MIGRANT FAMILIES FROM WESTERN MACEDONIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
In the past years, the emigration of population from the Republic of North Macedonia isa highly relevant topic. Special focus is given to the reasons for emigration which are mostlyidentified as economic reasons, i.e. low income rates, poor living standards, unemploymentand poverty. This paper analyzes emigration trends from Western Macedonia, a region thatis particularly affected by emigration flows in contemporary Macedonian history. The paperpresents detailed statistical data regarding emigrants from Western Macedonia according togender, origin, marital status, age, reasons for emigration, employment, education, ethnicity,etc. Additionally, the paper will present a research conducted during 2020 regarding migrantfamilies from Western Macedonia, their reasons for emigration, the changes that occurredafter the emigration process was completed, life contentment in the new country and thepossibility of returning to the homeland.